PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA ORGANISASI DENGAN TOTAL QUALITY MANAGEMENT SEBAGAI VARIABEL INTERVENING PADA PT. GANDAERAH HENDANA S & G BIOFUEL KABUPATEN PELALAWAN - Murdianto, Rahmat; Oemar, Yohanas; Indarti, Sri (Jurnal Tepak Manajemen Bisnis, 2016)
This study aims to analyze the influence of leadership and organizational culture on organizational performance with total quality management as an intervening variable in PT. Gandaerah Hendana S & G Biofuel Kabupaten Pelalawan with simultant.The study population were employees at PT . Gandaerah Hendana S & G Biofuel Kabupaten Pelalawan who work at the company. Determination of samples carried out in a non probability sampling. The total sample of 135 respondents were selected based on purposive sampling. Variables used are Organizational Performance as the dependent variable and leadership, organizational culture and total quality management as an independent variable . The analytical tool used is descriptive analysis and multiple linear regression using statistical tools wuth SPSS 17 for windows.The result of this study showed that leadership and organizational culture on organizational performance with total quality management as an intervening variable as simultant have influence of positive and significantly to organizational performance at PT. Gandaerah Hendana S & G Biofuel Kabupaten Pelalawan.As impllication, this research has been performed only on the crude palm oil factory. Therefore, for further research, its adding another contruction variables that can affect the organizational performance directly such as motivation, work environment and Organizational Commitment so that the organizational performance can be increase with significantly.